Negatively-Reinforced Mands: An Examination of Resurgence to Existing Mands in Two Children With Autism and Language Delays. (November 2016) - Chezan, Laura C.; Drasgow, Erik; Martin, Christian A.; Halle, James W.
In this study, we extended the literature on negatively-reinforced mands by teaching multiple novel, socially appropriate alternative mands to two young children with autism spectrum disorder (ASD). First, we replaced existing mands (e.g., pushing away) with two novel, socially appropriate, negatively-reinforced mands. Next, we examined responding under immediate- and delayed-reinforcement conditions to assess resurgence to existing mands and to determine whether the function of the communicative behavior influences the consistency with which different mands are emitted. Finally, we examined generalization to different social partners. Our data suggest that both children acquired the new mands and used them to avoid nonpreferred items. Resurgence to existing mands during delayed-reinforcement conditions was documented for one child, and the sequence in which mands were emitted within a response class was not influenced by the function of the communicative behavior. Generalization data indicate that both children emitted the new mands and one of the two children alternated between the two mands with a social partner who was not involved in the training. We discuss the importance of teaching multiple negatively-reinforced alternative mands to children with autism in applied settings.